An "inclusive congregational ministry" perspective on youth and children with a disability in South Africa - Dreyer, Yolanda (University of Pretoria, 2018)
The prevalence of children and youth living with a disability is a matter of concern on a national and international level. From a theological perspective the responsibility of faith communities toward children and youth with a disability is unquestionable. However, the question is whether this group of individuals benefit sufficiently from congregational ministry in South Africa. The father of a girl with Cerebral Palsy, Mr. H, made the following statement regarding the inclusion of children with a disability in faith communities: “It is not about putting up ramps. It is about breaking down walls ...” Mr. H.s’ statement inspired this investigation. According to him structural accessibility is not the main reason for the experience of their child feeling excluded from the faith community. He suggests that the “barriers” to inclusion experienced by them are based on other excluding factors. This study aims to determine whether the parents of other children with a disability share Mr.H.’s concerns, what these barriers are and how they can be overcome. The objectives of this study are the following:  to determine whether youth ministry in a postmodern context adequately reaches, includes and serves children and youth with a disability, in relation to the national statistics of children and youth living with a disability;  to determine the reasons why these children and youth with a disability experience exclusion from faith communities and youth ministry;  to investigate youth ministry from an “inclusive congregational approach” as a possible model to facilitate the inclusion of children and youth with a disability in South African faith communities. The first chapter is an introductory orientation of the situation of children and youth living with a disability nationally and internationally. The prevalent statistics of children and youth living with a disability indicate the scale of the challenge to faith communities to do effective ministry with this group of individuals in an inclusive way. The practical theological responsibility towards this group of individuals is discussed and the methodological positioning presented. From a postmodern perspective, the epistemological point of departure of this investigation is postfoundational and social constructionist. With regard to the latter especially the influence of social constructs with regard to disability is explored. The challenging topics of disability and disability culture are investigated in Chapter 3. This thesis focuses specifically on four types of disabilities, based on the prevalent statistics in South Africa. These disabilities are Cerebral Palsy, Down Syndrome, Autism and Deafness. It is of the utmost importance that congregants and clergy have insight into these disabilities and their effect on the children and youth in order to better understand their limitations, needs and challenges. Inclusive ministry to this group of individuals can only become a reality if there is a sound understanding of their circumstances and challenges. The empirical part of the investigation focuses on qualitative data gathered by means of structured interviews with the parents of five children and youth living with a disability and their experience as a family in various South African faith communities. By means of a quantitative survey data with regard to disability in congregations was procured. The results of the empirical investigation are brought into dialogue with the theoretical data regarding youth ministry and disability. This study aims to contribute to consciousness raising with regard to the inclusion and integration of children and youth with a disability in South African faith communities. It aims to benefit both the disability community as well as faith communities so that a more effective and inclusive ministry to children and youth with a disability can become a reality in churches in the country.